Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 215957 by LG last updated on 22/Jan/25

b^2 −4ac

b24ac

Commented by MathematicalUser2357 last updated on 23/Jan/25

x=((−b±(√(b^2 −4ac)))/(2a))

x=b±b24ac2a

Commented by ajfour last updated on 23/Jan/25

a(((−b±(√(b^2 −4ac)))/(2a)))^2 +b(((−b±(√(b^2 −4ac)))/(2a)))+c=0

a(b±b24ac2a)2+b(b±b24ac2a)+c=0

Terms of Service

Privacy Policy

Contact: info@tinkutara.com